2020
DOI: 10.1371/journal.pone.0239704
|View full text |Cite
|
Sign up to set email alerts
|

De-simplifying single-tablet antiretroviral treatments for cost savings in France: From the patient perspectives to a 6-month follow-up on generics

Abstract: In developed countries, most people living with HIV/AIDS are treated with costly brand single-tablet regimens. Given the economic impact, French guidelines recommend using generic antiretroviral therapy when possible to decrease antiretroviral therapy costs. We aimed to study HIV-infected patients' acceptability to switch from a brand single-tablet regimens [abacavir/lamivudine/dolutegravir (Triumeq ®) or emtricitabine/tenofovir disoproxil fumarate/rilpivirine (Eviplera ®)] to a treatment comprising of two pil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…The subset analysed for the primary outcome of generic PSI ADRs in the first-year-post-rollout included 5339 HIV-Tx and 8095 PrEP clients. Across all product versions, HIV-Tx clients were 83% male sex and median (Q1-Q3), age 52 (43-58) years, while PrEP clients were 99% male sex, age 33 (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42) years (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The subset analysed for the primary outcome of generic PSI ADRs in the first-year-post-rollout included 5339 HIV-Tx and 8095 PrEP clients. Across all product versions, HIV-Tx clients were 83% male sex and median (Q1-Q3), age 52 (43-58) years, while PrEP clients were 99% male sex, age 33 (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42) years (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Several single-clinic studies describe safe and effective de-simplification of single tablet ARV regimens to an equivalent multi-tablet combination including a generic NRTI product. [32][33][34] In Alberta, Canada, 19/257 (7.4%) clients who voluntarily initiated or switched to generic abacavir-lamivudine plus dolutegravir subsequently switched to the brand-name, single tablet equivalent after median 255 days (8.5 months) follow-up. In 2/257, (0.8%) a generic-related ADR was noted as the reason for change (one gastrointestinal upset, one allergic reaction).…”
Section: Discussionmentioning
confidence: 99%
“…This claim is buttressed by findings of Cantundo et al [18] whose study reported that patients on concomitant medications to address other health conditions asides HIV infection are prone to non-adherence to antiretroviral drugs. Furthermore, some researchers demonstrated that though the simplification of ARVs has helped in improving adherence, not all patients benefit from it as its effect can be counterbalanced by the effect on non-antiretroviral drugs taken by HIV positive individuals [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…De-simplifying STRs to two or three tablets once-daily regimens for cost savings was attempted in Calgary, Canada [35], France [36], and Denmark [37]. In these health care systems which emphasize health expenditure savings and societal altruism, de-simplification was accepted by ∼ 50% of patients approached in the Canadian and French study with preference for STR cited for those declining de-simplification.…”
Section: Potential Cost Savings With Strmentioning
confidence: 99%